THE INCLUSIVE FACE IN THE DIGITAL ERA: AN ANALYSIS OF THE IMPACT OF SYAFI'I MA'ARIF'S THOUGHTS ON WOMEN'S LEADERSHIP IN THE 21ST CENTURY - Syahriani, Fadilla; Yufriadi, Ferdi (Kafa`ah: Journal of Gender Studies, 2024)
This research explores the influence of Syafi'i Ma'arif's progressive and inclusive views on the role of women in leadership within the 21st-century digital era. Syafi'i Ma'arif, an esteemed Indonesian Muslim intellectual, has been instrumental in promoting gender equality and advocating for a more inclusive interpretation of Islamic principles, particularly regarding women’s rights and leadership roles. By employing a descriptive qualitative approach, this study examines Ma'arif's written works and draws insights from interviews with contemporary scholars and leaders inspired by his ideas. The analysis reveals that Ma'arif's emphasis on inclusivity challenges traditional gender norms and advocates for women's active participation in leadership across various sectors, including politics, education, and the economy. His forward-thinking perspective is especially relevant in the digital era, where the need for more inclusive leadership is increasingly recognized globally. Furthermore, the research highlights how Ma'arif’s views have resonated with contemporary Islamic thought, encouraging a re-evaluation of women's leadership roles in light of both religious teachings and modern societal demands. Through his works, Ma'arif has contributed to creating a framework for Islamic leadership that embraces diversity and promotes the empowerment of women. The study concludes that his thoughts provide valuable insights for addressing current challenges in promoting gender equality within Muslim-majority societies, particularly in navigating the complexities of the digital world.